Mothers and children without bread. Hunger in the Auxilio Social Cocinas de Hermandad and Comedores Infantiles during post-war Francoism (1939-1940) - Gloria Román Ruiz (Culture & History Digital Journal)
This article analyses one of the main social policies in post-war Spain: the welfare policies of Auxilio Social. In particular, it explores the conditions and daily operation of the Comedores Infantiles and Cocinas de Hermandad run by that Falangist institution in Madrid in the immediate postwar period (1939 and 1940). This work sustaines that the rations served in these charitable-assistance institutions were fewer, smaller, and of worse quality than officially recognised. Therefore, the food given to the needy mothers and children at these Auxilio Social premises was insufficient to quell their hunger. Moreover, since the facilities did not meet the minimum conditions of size, cleanliness, ventilation, and kitchen utensils, the attendees were exposed to infectious diseases. It is also argued that, beyond the food supply problems of those famine years, the ineffectiveness of the Comedores and Cocinas was often due to the staff who worked in them, as they often used to steal food for their own consumption or to sell on the black market. Finally, it is argued that, given its failure to feed the needy, Auxilio Social’s aim of extending support to the dictatorship through the guise of charity was tarnished.